2023
DOI: 10.1386/fspc_00117_1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring female consumers’ preferred evaluative criteria for casual clothing purchases and the association with body shape

Abstract: The association between clothing fit and body shape is vital to purchasing satisfaction. However, scant research is available on female consumers’ use of this criterion to determine whether an apparel item will suit their body shape. The purpose of this study was to determine the association between female consumers’ perceived body shape and the evaluative criteria they frequently use when making casual clothing purchasing decisions. A group-administered questionnaire was used to collect purposeful and conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They differed significantly from the proportions of other evaluative criteria for the size-fit garment. A study conducted by Kempen, Kasambala, and Tobias-Mamina (2022) on African women found that body shape was an important criterion when choosing a blouse/top, while the dress was significantly associated between fit/sizing and women with an hourglass body shape comfort and the triangle body shape, and color/patterns and the rectangular body shape. The results showed that variations in body shapes are crucial when it comes to apparel fit and need to be improved for certain prominent body shapes.…”
Section: Psychological Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…They differed significantly from the proportions of other evaluative criteria for the size-fit garment. A study conducted by Kempen, Kasambala, and Tobias-Mamina (2022) on African women found that body shape was an important criterion when choosing a blouse/top, while the dress was significantly associated between fit/sizing and women with an hourglass body shape comfort and the triangle body shape, and color/patterns and the rectangular body shape. The results showed that variations in body shapes are crucial when it comes to apparel fit and need to be improved for certain prominent body shapes.…”
Section: Psychological Comfortmentioning
confidence: 99%
“…The results showed that variations in body shapes are crucial when it comes to apparel fit and need to be improved for certain prominent body shapes. Based on Kempen, Kasambala, and Tobias-Mamina (2022) showed that body shape has a strong association with comfort and fitness. Most garments had fit problems since pattern measurements were adjusted based on the Silhouette (Jalil & Shanat, 2022).…”
Section: Psychological Comfortmentioning
confidence: 99%